Influence of rural environment on diagnosis, treatment, and prognosis of colorectal cancer. Issue 4 (August 1992) - Launoy, G; Le Coutour, X; Gignoux, M; Pottier, D; Dugleux, G
Abstract : STUDY OBJECTIVE–Several studies have shown that residential location (urban or rural) influences the incidence of colorectal cancer. The aim was to investigate the influence of rural environment on colorectal cancer history and survival in a well defined population. DESIGN–Patients with colorectal cancer diagnosed in the department of Calvados (France) were classified by place of residence (urban/rural) and information on clinical symptoms, tumour extension, treatment, and survival was collected. SETTING–The study was population based, in the department of Calvados in France. PATIENTS–During 1978-1984, 1445 colorectal cancers were collected by the Digestive Tract Cancer Registry of Calvados, 1047 with an urban place of residence (544 males and 503 females) and 284 with a rural place of residence (134 males and 150 females). MEASUREMENTS AND MAIN RESULTS–In both sexes, rural patients with colorectal cancers were treated less frequently in a specialised health care centre (40.0%) than patients from an urban population (53.4%). The difference was mainly but not entirely explained by distance from the specialised health care centre. In females in the rural population, cancers were diagnosed more frequently at the stage of severe clinical symptoms (22.1%) and metastases (18.8%) than they were in the urban population (15.5% and 12.3%). In addition among females a rural environment appeared to confer a worse prognosis (relative risk = 1.3). CONCLUSIONS–Our findings suggest an inequality between rural and urban populations, especially for women. The loneliness of rural women leads to a delay in diagnosis and worse survival. In health education campaigns on colorectal cancer, efforts must be made to provide medical information to rural women in order to reduce the delay in diagnosis and improve survival.